Synthesis of Gold Nanoparticles and Their Interaction with Polypyrrole - Chauhan, Arvind (My University, 2010)
Gold Nanoparticles were synthesized by chemical synthesis route. Sodium citrate acted as reducing as well as stabilizing agent in the synthesis of gold nanoparticles. These Au nanoparticles were characterized by UV-Vis. Different chemical and electrochemical methods are generally used in the synthesis of polypyrrole. Despite many interesting applications, the use of polypyrrole is limited because of difficulty in processing it. Several approaches have been explored to improve the ability to process polypyrrole, including the use of emulsion, inverse emulsion, steric stabilizer, and micro emulsion methods. The study involves the synthesis of polypyrrole (PPY) and polypyrrole composite of gold (PPY-Au) by polymerization procedure. Size, shape and morphology of the synthesized particle were analyzed by X-ray diffraction, TEM analytic techniques.
M.Tech. (Materials & Metallurgical Engineering)
Keywords: gold nanoparticles,polypyrrole